Cash and Conflict: Large-Scale Experimental Evidence from Niger - Patrick Premand; Dominic Rohner (Center for Economic Studies and ifo Institute (CESifo), 2023)
Conflict undermines development, while poverty, in turn, breeds conflict. Policy interventions such as cash transfers could lower engagement in conflict by raising poor households' welfare and productivity. However, cash transfers may also trigger appropriation or looting of cash or assets. The expansion of government programs may further attract attacks to undermine state legitimacy. To investigate the net effect across these forces, this paper studies the impact of cash transfers on conflict in Niger. The analysis relies on the large-scale randomization of a government-led cash transfer program among nearly 4,000 villages over seven years, combined with geo-referenced conflict events that draw on media and nongovernmental organization reports from a wide variety of international and domestic sources. The findings show that cash transfers did not result in greater pacification but-if anything-triggered a short-term increase in conflict events, which were to a large extent driven by terrorist attacks by foreign rebel groups (such as Boko Haram) that could have incentives to "sabotage" successful government programs.
Keywords: D74; I38; O17; 330; conflict; terrorism; cash transfers; Sahel